Study of Timothy herb mineral composition - Bondarenko, Igor; Kyslychenko , Viktoriya (Annals of Mechnikov’s Institute, 2023)
Introduction. Higher plants are the primary food source of mineral compounds for many living creatures. At least 50 types of different nutrients (12 vitamins, 8 amino acids, 17 mineral elements, etc.) are necessary for normal human activity. For a person, as a consumer of plant raw material, the ability of plants to accumulate individual elements, as well as the possibility of their quantitative transition directly to the product, is of great importance. It was determined that the transition of elements from plant raw material into aqueous forms (either decoctions or infusions) is 8-28%. The elements affect the activity of many enzymes, are part of vitamins, hormones and thereby support the homeostasis of the body. Their study has been the subject of numerous scientific researches since the middle of the last century. Therefore, it is promising to search for new plant sources that can be used in the treatment and prevention of conditions caused by a deficiency of mineral elements. The aim of the work was to obtain information on the quantitative content and qualitative composition of macro- and microelements in the timothy herb in order to create effective and safe medicines on its basis. Materials and methods. Timothy herb harvested in August 2022 in the Kharkiv region (Ukraine) was used for the study. The mineral composition analysis was carried out on the basis of the State Scientific Institution "Institute for Single Crystals" of the National Academy of Sciences of Ukraine (Kharkiv). The tests were done using the atomic absorption spectrographic technique with atomization in an air-acetylene flame according to the State Pharmacopoeia of Ukraine 2.0, vol. 1. Samples atomization was performed on graphite electrodes of the IBC-28 device in an alternating current arc discharge (I = 16 A, U = 220 V, t = 60 sec, Р = 0.04 MPa, tflame = 2250 °C). Spectra were recorded using a DFS-8 spectrograph (diffraction grating 600 pcs/mm with a three-lens slit illumination system). The emission lines intensity in the spectra was recorded with a MF-1 microphotometer (ignition phase 60 °C, spectrograph slit width 0.015 mm, λ = 196–706.5 nm). For identification and quantitative determination of the elemental composition of the studied plant material, the corresponding absorption bands according to standard samples were used (nm): 213.9 (Zn); 228.8 (Cd); 232.0 (Ni); 240.7 (Co); 248.3 (Fe); 251.6 (Si); 257.0 (Hg); 279.5 (Mn); 283.3 (Pb); 285.2 (Mg); 309.3 (Al); 313.3 (Mo); 324.7 (Cu); 357.9 (P); 365.0 (As); 422.6 (Ca); 460.0 (Sr); 589.0 (Na); 706.5 (K). Photographic plates were developed, dried, photometered lines (in nm) of the spectra of samples, calibration samples, as well as the background near them. Then a calibration graph was constructed in coordinates: the average value of the difference between the blackening of the line and the background is the logarithm of the element content in the calibration samples, by which the percentage content of the element in the ash was found and its quantitative content in the studied plant raw material (mg/100 g) was calculated. The determination of total ash content was carried out according to the prolotocol described in the State Pharmacopoeia of Ukraine 2.0, vol. 1, general article 2.4.16 "Total ash". Statistica 8 software (StatSoft inc., USA) and the package of statistical functions of the Microsoft Excel were used for the obtained results data analysis. Results and discussion., The quantitative content of 19 mineral compounds was identified and determined in timothy herb by atomic absorption spectrometry technique. 10 of the identified mineral compounds (Ca, Cu, Fe, K, Mg, Mn, Zn, Co, P, Mo) are essential. Macroelements (mg/100 g) such as K (4600.00 ± 410.60), Si (1500.00 ± 110.70), Ca (1170.00 ± 124.80), as well as microelements such as Al (110.00 ± 10.18) and Fe (39.00 ± 4.33) were accumulated in predominant concentrations. The total content of mineral compounds was 8651.42 mg/100 g, of which macroelements – 8470.00 mg/100 g, microelements – 181.42 mg/100 g. The mineral elements content in timothy herb gradually decreased in the series K > Si > Ca > Mg > P > Na > Al > Fe > Zn > Mn > Sr > Cu > Ni > Mo > Pb. Accumulation of toxic heavy elements (Cd, Co, Hg, Pb, As,) for the studied plant material was <0.01-0.03 mg/100 g, which is within the permissible norms for medicinal plant raw materials, established by the State Pharmacopoeia of Ukraine 2.0, vol. 1. As a result of the analysis, it was determined that the ash content in timothy herb equaled 15.57 ± 0.76%. Conclusions. For the first time, the quantitative content of 19 mineral compounds was identified and quantified in timothy herb by atomic absorption spectrometry. Potassium, silicon, calcium, aluminum and ferrum are dominant. Heavy metals are identified within permissible limits, so timothy herb is quite safe for use. The obtained data allow us to note that timothy herb contains significant amounts of many important mineral compounds, primarily essential ones. In a complex with other biologically active substances (polysaccharides, phenolic compounds, organic acids), this emphasizes the therapeutic significance and enables the creation of new drugs of combined action based on the investigated plant raw material. Keywords: timothy, Phleum pratense L., mineral compounds, atomic absorption spectrometry, identification, quantitative content.